Renal candidiasis associated with papillary necrosis in a captive tiger (Panthera tigris) - Floyd D. Wilson; Brittany Baughman; Michael J. Mauel; Michael Holifield; Donna Todd; Lanny Pace (Veterinary Medicine and Science, 2024)
Abstract A 14‐year‐old male tiger developed anorexia with elevated blood urea nitrogen and creatinine levels. The patient had a palpable abdominal mass and demonstrated neutrophilic leukocytosis and anaemia. Leukocytes, yeast and bacteria were present in the urine. The animal was non‐responsive to therapy and was subsequently euthanised. Extensive acute renal papillary necrosis (RPN) with pyelonephritis, chronic nephritis and polycystic renal disease were evident during gross and microscopic pathology examinations. The histologic occurrence of fungal spores and pseudohyphae morphologically consistent with Candida species were observed within the necrotic papillary regions of the kidney and within multiple foci of mild parakeratotic hyperkeratosis present in the gingiva and tongue. Candida albicans along with a slight growth of Escherichia coli were recovered from kidney cultures. Possible contributory factors for the renal candidiasis and associated RPN include predisposing oral candidiasis, polycystic renal disease, ischaemic nephrosclerosis, age‐associated or other forms of immunodeficiency and therapy with meloxicam, a non‐steroidal anti‐inflammatory drug. The absence of apparent lower urinary tract involvement coupled with the presence of intravascular renal ‘Candida emboli’ suggest that chronic oral candidiasis was the probable source of the kidney infection.